A systematic review on silica-, carbon-, and magnetic materials-supported copper species as efficient heterogeneous nanocatalysts in “click” reactions - Shiri, Pezhman; Aboonajmi, Jasem (Beilstein Journal of Organic Chemistry, 2020)
In recent years, many inorganic silica/carbon-based and magnetic materials have been selected to arrest copper ions through a widespread range of anchoring and embedding methodologies. These inorganic supported nanocatalysts have been found to be efficient, environmentally friendly, recyclable, and durable. In addition, one of the vital issues for expanding new, stable, and reusable catalysts is the discovery of unique catalysts. The basis and foundation of this review article is to consider the recently published developments (2014–2019) in the synthesis and catalytic applications of copper supported by silica nanocomposites, carbon nanocomposites, and magnetic nanocomposites for expanding the “click” chemistry.
Keywords: “click” reaction; copper complexes; reusable catalysts; Sharpless–Meldal C–N bond-forming reaction; silica/carbon/magnetic materials